Serum luteinizing hormone, follicle-stimulating hormone and oestradiol pattern in women undergoing pituitary suppression with different gonadotrophin-releasing hormone analogue protocols for assisted reproduction - Manna, Claudio; Rahman, A; Sbracia, M; Pappalardo, S; Mohamed, E I; Linder, Roland; Nardo, L G (Gynecological endocrinology : the official journal of the International Society of Gynecological Endocrinology, 2005)
Gonadotrophin-releasing hormone analogues (GnRH-a) are used widely in controlled ovarian stimulation (COS) cycles for assisted reproduction. At present, there is great debate about the influence of exogenous hormone activity on the hypothalamus-pituitary axis following pituitary desensitization. The objective of this comparative study was to investigate the pattern of luteinizing hormone (LH), follicle-stimulating hormone (FSH) and oestradiol in women undergoing ovarian stimulation with different GnRH-a preparations. We retrospectively analysed 201 women, aged between 27 and 43 years, who were referred consecutively to our infertility clinic between January 2002 and January 2003. All women had no endocrinopathies or occult ovarian failure as assessed by day-3 hormone profile. Women were enrolled in one of the following COS protocols: depot triptorelin long protocol (n = 38), buserelin long protocol (n = 101) or buserelin short protocol (n = 62). Recombinant FSH was used to induce ovulation. Treatment was monitored by transvaginal ultrasound scan and serum measurement of FSH, LH and oestradiol. Among the women initially included, 30 had cancelled cycles due to poor ovarian response. Serum LH levels were significantly higher in the short-protocol group compared with the long-protocol groups (p < 0.001). The number of follicles, oocyte yield, number of grade-I embryos and fertilization rate were significantly lower in the short-protocol group than in the long-protocol groups. These findings showed that LH concentrations are significantly higher in women undergoing reversible medical hypophysectomy with a GnRH-a short protocol than in women treated with a long protocol. The hypothesis of an LH ceiling is confirmed.
Keywords: Adult; Area Under Curve; Buserelin; Estradiol; Female; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Humans; Luteinizing Hormone; Male; Ovulation Induction; Retrospective Studies; Sperm Injections, Intracytoplasmic; Triptorelin Pamoate